A 21-year-old woman with mediastinal mass and cardiac arrest. (19th June 2013) - Al-Sanouri, Ibrahim; Shaban, Mohammad; Al-Shahid, Maie; Abdulaziz, Salman
Abstract : Mediastinal mass syndrome (MMS) is a devastating respiratory and haemodynamic condition that might be encountered postintubation if special precautions are not carefully undertaken. We describe a case of MMS in a 21-year-old woman with a fatal outcome following emergency intubation for acute respiratory failure.